2004
DOI: 10.1038/ncb1086
|View full text |Cite|
|
Sign up to set email alerts
|

A physical and functional map of the human TNF-α/NF-κB signal transduction pathway

Abstract: Signal transduction pathways are modular composites of functionally interdependent sets of proteins that act in a coordinated fashion to transform environmental information into a phenotypic response. The pro-inflammatory cytokine tumour necrosis factor (TNF)-alpha triggers a signalling cascade, converging on the activation of the transcription factor NF-kappa B, which forms the basis for numerous physiological and pathological processes. Here we report the mapping of a protein interaction network around 32 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
695
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 964 publications
(752 citation statements)
references
References 25 publications
26
695
2
3
Order By: Relevance
“…Tandem-affinity purification and peptide mass fingerprinting identified A20-binding inhibitor of NF-κB 2 (ABIN-2) as an NF-κB1 p105-interacting protein [56,57]. Cotransfection experiments indicate that ABIN-2 can also interact directly with TPL-2, but preferentially forms a ternary complex with p105 and TPL-2.…”
Section: Regulation Of Tpl-2 Stability By Abin-2mentioning
confidence: 99%
“…Tandem-affinity purification and peptide mass fingerprinting identified A20-binding inhibitor of NF-κB 2 (ABIN-2) as an NF-κB1 p105-interacting protein [56,57]. Cotransfection experiments indicate that ABIN-2 can also interact directly with TPL-2, but preferentially forms a ternary complex with p105 and TPL-2.…”
Section: Regulation Of Tpl-2 Stability By Abin-2mentioning
confidence: 99%
“…In a landmark report aimed at mapping the entirety of the interaction network of the TNF-α/NF-κB signal transduction pathway by AP-MS, MEKK3 was found in association with the majority of RPAP3/R2TP/prefoldin-like complex subunits (Bouwmeester et al 2004). Indeed, RPAP3 (FLJ21908), PIH1D1 (FLJ20643), RUVBL1, RUVBL2, PFDN2, PFDN6 (HKE2), PDRG1 (C20orf126) and C19orf2 all copurified with MEKK3, as did the CCT complex and Hsp90α/β.…”
Section: Map3k3 (Mekk3)mentioning
confidence: 99%
“…One mutation tested was the same as that initially identified in a tumor from a colorectal cancer patient (Kinzler et al, 1991). Particularly interesting is the finding that MCC appears to stabilize the IkBb protein that is an essential inhibitor of NF-kB transcription factor activation (Bouwmeester et al, 2004). There is evidence that NF-kB activation is involved in colorectal carcinogenesis (Karin et al, 2002) and that it can be caused by the BRAF V600E mutation in vitro (Ikenoue et al, 2003).…”
Section: Serrated Polypsmentioning
confidence: 99%
“…Early reports indicated that loss of heterozygosity (LOH) at the MCC locus is common, that is, B42% in colorectal cancers (Ashton-Rickardt et al, 1991), whereas somatic mutation of MCC is relatively rare, 3-7% (Nishisho et al, 1991). More recent studies have shown that the wild-type MCC protein may have a functional role in important cellular processes relevant in carcinogenesis, such as cell cycle regulation and the nuclear factor-kB (NF-kB) pathway (Matsumine et al, 1996;Bouwmeester et al, 2004). The activation and translocation of NF-kB to the nucleus is part of a signal-transduction pathway, which forms a basis for several physiologic and pathologic processes including cancer.…”
Section: Introductionmentioning
confidence: 99%